Magnetization reversal and microstructure in polycrystalline Fe50Pd50 dot arrays by self-assembling of polystyrene nanospheres. Issue 1 (1st December 2016) - Tiberto, Paola; Celegato, Federica; Barrera, Gabriele; Coisson, Marco; Vinai, Franco; Rizzi, Paola
Abstract: Nanoscale magnetic materials are the basis of emerging technologies to develop novel magnetoelectronic devices. Self-assembly of polystyrene nanospheres is here used to generate 2D hexagonal dot arrays on Fe50 Pd50 thin films. This simple technique allows a wide-area patterning of a magnetic thin film. The role of disorder on functional magnetic properties with respect to conventional lithographic techniques is studied. Structural and magnetic characteristics have been investigated in arrays having different geometry (i.e. dot diameters, inter-dot distances and thickness). The interplay among microstructure and magnetization reversal is discussed. Magnetic measurements reveal a vortex domain configuration in all as-prepared films. The original domain structure changes drastically upon thermal annealing performed to promote the transformation of disordered A1 phase into the ordered, tetragonal L10 phase. First-order reversal magnetization curves have been measured to rule out the role of magnetic interaction among crystalline phases characterized by different magnetic coercivity. Abstract :